Impact of power ultrasound on the quality of leafy green produce through a multifrequency, multimode, modulated system - Bin Zhou; J. Atilio de Frias; Yaguang Luo; Jorge M. Fonseca; Hao Feng (Ultrasonics Sonochemistry)
Ultrasound technology has been increasingly explored as an eco-friendly method to improve the microbial safety of leafy greens. However, its effect on produce quality is critical, and considerable knowledge gaps remain in this area. The present study examined the response of leafy greens to ultrasound treatment as shown by tissue damage and sensory quality, using a novel multifrequency, multimode, modulated (MMM) system to address the issue of nonuniform ultrasound field distribution. Iceberg lettuce, romaine lettuce, spinach, loose leaf lettuce and Lollo Rosso were subjected to different ultrasonication durations (1–16 min) in a MMM tubular treatment unit at 34 kHz and subsequently stored at 1 °C for three weeks. Sensory evaluations by a trained panel and electro-conductivity rate measurements were conducted to assess produce quality over time. Ultrasound treatment at an acoustic power density below 80 W/L had no significant effect (P > 0.05) on the overall sensory quality of leafy greens during 14 days of storage. Even though the electro-conductivity rate, an indicator of tissue damage, increased in ultrasound-treated samples compared to control, it did not result in perceptible changes in sensory attributes.